SAT0540 ONE-YEAR OUTCOMES AFTER RHEUMATIC IMMUNE-RELATED ADVERSE EVENTS FROM CHECKPOINT INHIBITORS. (2nd June 2020) - Berard, E.; Barnetche, T.; Rouxel, L.; Dutriaux, C.; Dousset, L.; Prey, S.; Beylot-Barry, M.; Seneschal, J.; Veillon, R.; Vergnenegre, C.; Daste, A.; Domblides, C.; et al.
Abstract : Background: Description and initial management of rheumatic immune-related adverse-events (irAEs) from cancer immunotherapies have been reported by several groups but to date, few studies have evaluated the long-term outcomes and management of rheumatic irAEs (1). Objectives: To describe the long-term management and assess the one-year outcomes of patients who experienced rheumatic immune-related adverse events (irAEs) due to immune checkpoint inhibitors (ICI). Methods: This was a single-centre prospective observational study including patients referred for musculoskeletal symptoms while treated with ICI. After baseline rheumatological evaluation defining the clinical entity presented, follow-up visits were organised according to the type and severity of irAE. At one year, persistence of irAE, ongoing treatment, as well as cancer outcomes were assessed. Results: 63 patients were included between September 2015 and June 2018. 24 patients (38%) presented with non-inflammatory musculoskeletal conditions managed with short-term symptomatic treatment and did not require specific follow-up. 39 patients (62%) experienced inflammatory manifestations, mimicking either rheumatoid arthritis (RA, n=19), polymyalgia rheumatica (PMR, n=16), psoriatic arthritis (PsA, n=3) and one flare of a preexisting axial spondyloarthritis. Overall, 32 patients (82%) received systemic glucocorticoids, with a median rheumatic dosage of 15mg/day (range: 5-60mg/day). None of the patients had to permanently discontinue ICI therapy for rheumatic irAE. 20 patients (67%) were still receiving glucocorticoids at one year, with a median dosage of 5mg/day (range: 2-20mg/day). Glucocorticoids were more frequently discontinued for patients with RA-like condition (44%) than PMR-like condition (23%), but no other predictive factor of glucocorticoids withdrawal could be identified. At one year, overall survival and progression-free survival were comparable between patients who were still receiving glucocorticoids for rheumatic irAE and patients who have discontinued. Eight patients required csDMARDs. Conclusion: At one year, a majority of patients required long-term low-dose glucocorticoids for chronic rheumatic irAE, which seems not altering oncological control. References: [1]Braaten TJ, Brahmer JR, Forde PM, et al. Immune checkpoint inhibitor-induced inflammatory arthritis persists after immunotherapy cessation. Ann Rheum Dis. 2019 Sep 20. Disclosure of Interests: None declared